Inefficient intramolecular vibrational energy redistribution for the H + HO2 reaction and negative internal energy dependence for its rate constant - Jasper, Ahren W.; Moberg, Daniel R.; Tao, Yujie; Klippenstein, Stephen J.; Sivaramakrishnan, Raghu (Frontiers in Physics, 2022)
Quasiclassical trajectories (QCT) and newly constructed global potential energy surfaces are used to compute thermal and nonthermal rate constants for the H + HO2 reaction. The thermal QCT rate constants are up to 50% smaller than transition state theory (TST) rate constants based on the same level of electronic structure theory. This reduction is demonstrated to result from inefficient intramolecular vibrational energy redistribution (IVR) in the transient H2O2 well, with a significant fraction of trajectories that reach the H2O2 well promptly dissociating back to reactants instead of via the heavily statistically favored 2OH channel. The nonstatistical reduction factor, kIVR, that quantifies this effect is shown to increase in importance with temperature, with kIVR = 0.81 at 300 K and 0.47 at 2500 K. Finally, we show that inefficient IVR causes H + HO2 rate constants mediated by H2O2 to depend inversely on the initial vibrational excitation of HO2.